Towards a transformation in the pharmacist care paradigm: A scoping study (2017)
Introduction: In a paper published by Hepler, it is mentioned that the Pharmaceutical Care constitutes a change in the paradigm of the profession, an affirmation that itis necessary to clarify since apparently, this concept is not used from the philosophy or the social sciences. Methodology: A scoping study was performed from systematicsreviews of literature and meta-analysis published in MEDLINE, EMBASE and LILACS, which the role of the pharmacist in the different settings of health carewas studied. It was not restricted by language or date of publication. Results: The selection process identifies 86 reviews published between 1998 and 2014, of which 84.9% are Systematic Review (SR). It was studied all care settings 23.3%, community 22.1%, and ambulatory setting 22.1%. According to the title, 65% referring to the role of the pharmacist, 21% with pharmaceutical care or other related terms and 14% with clinical pharmacy services. There is no uniformity in the concepts of pharmaceutical care or drugs related problems. Conclusions: It is necessary to construct the knowledge object of pharmaceutical care activities from a paradigm that allowsanother understanding of pharmacist interventions, construct values in the patientpharmacist relationship supported in Latin American bioethics and a methodology of research that transcends the findings of the performed studies using the designs of classical epidemiology.